NURSE INTERPERSONAL COMMUNICATION SKILLS INFLUENCE THE INCREASING OF PATIENT SATISFACTION - Richard, Selvia David; Hanafi, Imam (Jurnal Penelitian STIKES Kediri, 2012)
In nursing practice, communication is a means of developing relationships nurses and patients, and may affect the level of satisfaction of patients to health care that is given. The purpose this research was to study the effects of nurse interpersonal communication toward patient at Baptist Hospital Kediri. The design of this study was cross-sectional with the independent variable was nurse interpersonal communication and the dependent variable was level of patient satisfaction. Population of this study was patients IRNA Class 3 RS. Baptist Kediri, it was obtained Â 96 patients, using Â proposive sampling technique. Statistical analysis using Spearman's rho test with Î± â‰¤ 0.05. The results obtained were good nurses interpersonal communication, while the level of patient satisfaction with the services of nursing is very satisfied, statistical tests obtained p = 0.000 means that there is an influence on the level of interpersonal communication in patient satisfaction IRNA Class 3 RS. Baptist Kediri. Concluded that if the interpersonal communication skills of high nurse patient will be more satisfied.